Molecular genetic typing reveals further insights into the diversity of animal-associated Staphylococcus aureus - SMYTH, CYRIL JAMES; HARTIGAN, PATRICK JAMES (My University, 2009)
Staphylococcus aureus is an important pathogen of man, but is also able to colonize and cause disease in a wide variety of mammals and birds. An extended multilocus sequencing approach, involving multilocus sequence typing (MLST), sas typing, spa typing and agr typing, was used to examine the molecular diversity of 118 S. aureus isolates recovered from a range of host species and to compare these data with the known diversity of human-derived isolates. MLST revealed that the commonest animal-associated MLST types were ST133, ST5, ST71, ST97, ST126 and ST151. ST133 appears to be an ungulate-animal-specific genotype, as no evidence of ST133 associating with humans has yet been found in the literature. Novel and unique sas alleles were identified in the animal-associated strains that may represent animal-associated sas alleles. However, sas typing exhibited a lower typeability than MLST for the animal strains (91.3 %). Phylogenetic analyses using neighbour-joining and maximum-parsimony trees localized ruminant-associated MLST lineages to both previously identified S. aureus subspecies aureus subgroups, thus explaining the finding of all four agr types within the ruminant-associated strains. S. aureus isolates recovered from chickens and rabbits were genotypically more similar to known human genotypes than the ruminant-associated lineages.
PUBLISHED
Keywords: Infectious Diseases; Staphylococcus aureus